A semiotic perspective of mathematical activity: The case of integer - Ratni Purwasih; Turmudi Turmudi; Jarnawi Afgani Dahlan; Edi Irawan; Sona Minasyan (Jurnal Infinity, 2024)
Semiotics is defined as using signs to represent mathematical concepts in problem-solving. The mathematical semiotic process involves creating meaning from the triadic relationship between the representamen (R), object (O), and interpretant (I). Mathematical semiotics play an essential role in the cognitive processes of individuals as they formulate and communicate mathematical ideas. Therefore, this study aims to describe the stages of the semiotic process of junior high school students solving integers-related mathematical problems. In this qualitative analysis, the participant is a seventh-grade student categorized as pseudo-semiotic. The research instrument is a test on integers and interviews. The results demonstrate that the semiosis related to integers involves the representamen, object, and interpretant stages. For a subject with a pseudo-semiotic type, this meaning-making process requires the construction of a comprehensive understanding of the concept. Furthermore, the understanding is developed using various instruments, resulting in connection conflicts between different components of the semiotic system. Connection conflict occurs because of the mismatched relationship between the elements of semiosis: representamen, object, and interpretant. A pseudo-semiotic subject only has a superficial understanding of mathematical concepts, making it challenging to establish accurate connections between symbols and their underlying meanings. Consequently, this hinders the ability to understand mathematics profoundly and apply the concepts in real-life situations.